2011
DOI: 10.1021/cb2002686
|View full text |Cite
|
Sign up to set email alerts
|

Diazo Reagents with Small Steric Footprints for Simultaneous Arming/SAR Studies of Alcohol-Containing Natural Products via O–H Insertion

Abstract: Natural products are essential tools for basic cellular studies leading to the identification of medically relevant protein targets and the discovery of potential therapeutic leads. The development of methods that enable mild and selective derivatization of natural products continues to be of significant interest for mining their information-rich content. Herein, we describe novel diazo reagents for simultaneous arming and structure-activity relationship (SAR) studies of alcohol-containing natural products wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…We recently described several mild, microscale methods for simultaneous arming and SAR studies of natural products to address these issues including a Rh(II)-catalyzed OH and NH insertion of natural products bearing alcohols or amines, 12,13 a mild In(III)-catalyzed iodination of arene-containing natural products, 14 and cyclopropanations of natural products bearing both electron rich and deficient alkenes. 15 These functionalization methods are dependent on the presence of native functional groups and are thus limited in terms of positional diversity.…”
mentioning
confidence: 99%
“…We recently described several mild, microscale methods for simultaneous arming and SAR studies of natural products to address these issues including a Rh(II)-catalyzed OH and NH insertion of natural products bearing alcohols or amines, 12,13 a mild In(III)-catalyzed iodination of arene-containing natural products, 14 and cyclopropanations of natural products bearing both electron rich and deficient alkenes. 15 These functionalization methods are dependent on the presence of native functional groups and are thus limited in terms of positional diversity.…”
mentioning
confidence: 99%
“…In a subsequent report, the same group introduced alkynyl diazo ester 7b that features a smaller steric footprint, an α-trifluoroethyl versus p -bromophenyl substituted ester, and demonstrated that otherwise identical FK506 derivatives ( 8b and 8c ) exhibited markedly different interactions with known protein targets validating the large steric differences between these seemingly similar derivatives ( vide infra ). 28 …”
Section: Systematic Chemo- and Site-selective Derivatizations Of Namentioning
confidence: 99%
“…2728 Toward studying the effect on biological activity that different α-substituents on the derived ethers generated through O–H insertions might have ( i.e . α-trifluoroethyl versus p -bromophenyl, see Scheme 3 for structures), a set of diastereomeric FK506-derived ethers 8b–c , were separated and used in cellular assays and affinity chromatography experiments with biotin derived conjugates.…”
Section: Applications To Cellular Probe Synthesis and Biological Stmentioning
confidence: 99%
“…For this reason, we set out to develop chemo- and site selective methods to alter the structure of native natural products for structure-activity relationship (SAR) studies, generate new natural product-like structures, and to rapidly synthesize natural product-based cellular probes including biotin, fluorophore, and photoaffinity natural product conjugates. 4 To date, we have described methods for simultaneous arming and SAR studies of natural products employing mild Rh(II)-catalyzed O-H insertions with alkynyl diazo acetates of alcohol-containing natural products 5 and In(OTf) 3 -catalyzed iodination of arene-containing natural products. 6 To expand these derivatizations to other commonly found functional groups, we now report the development of mild and selective cyclopropanation reactions of both electron-rich and electron-poor olefins.…”
mentioning
confidence: 99%
“…The reaction of more sterically encumbered alkenes was more challenging as evidenced by attempted cyclopropanation of forskolin which required 3 equiv of diazo ester 2d for complete conversion to deliver cyclopropanes 8 in 81% yield. To prevent OH insertion 5 with accessible free alcohols, mild global silylation was performed prior to cyclopropanation of forskolin and gibberellic acid methyl ester. However, in the case of forskolin, the hindered tertiary C6 and secondary C9 alcohols are not protected under these conditions and also did not undergo OH insertion.…”
mentioning
confidence: 99%